2015
DOI: 10.1016/j.apsusc.2015.05.153
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of silicon nanocrystals embedded in silicon carbide: Comparison of single layers and multilayer structures

Abstract: The outstanding demonstration of quantum confinement in Si nanocrystals (Si NC) in a SiC matrix requires the fabrication of Si NC with a narrow size distribution. It is understood without controversy that this fabrication is a difficult exercise and that a multilayer (ML) structure is suitable for such fabrication only in a narrow parameter range. This parameter range is sought by varying both the stoichiometric SiC barrier thickness and the Si-rich SiC well thickness between 3 and 9 nm and comparing them to s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…The former is crucial for the quantum confinement effect, and the latter causes a high defect density and therefore extremely short lifetimes, making a definitive proof of quantum confinement -to the best of the authors' knowledge -impossible until now. In a prior study, we showed that the Si NC size can be controlled by the Si content of the SixC1-x layers [12]. In the present work, we tried to reduce SiC crystallization by reducing the annealing time.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The former is crucial for the quantum confinement effect, and the latter causes a high defect density and therefore extremely short lifetimes, making a definitive proof of quantum confinement -to the best of the authors' knowledge -impossible until now. In a prior study, we showed that the Si NC size can be controlled by the Si content of the SixC1-x layers [12]. In the present work, we tried to reduce SiC crystallization by reducing the annealing time.…”
Section: Introductionmentioning
confidence: 92%
“…The three different layer compositions of x = 0.50, x = 0.63 and x = 0.77 used in this work were previously determined by Rutherford backscattering spectrometry with an accuracy of 1% [17]. The associated gas fluxes can be found in our previous work [12].…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations